2015
DOI: 10.5588/ijtld.14.0679
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis among nomads in Adamawa, Nigeria: outcomes from two years of active case finding

Abstract: Nomads in Nigeria have high TB rates, and active case-finding approaches may be useful in identifying and successfully treating them. Large-scale interventions in vulnerable populations can improve TB case detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 0 publications
3
50
0
Order By: Relevance
“…Consistent with previous studies, 16,17 our study found that Xpert performed well in community-based ACF, especially when compared with culture. Xpert detected all the culture M. tuberculosis -positive cases and yielded three additional diagnoses in a much shorter turnaround time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies, 16,17 our study found that Xpert performed well in community-based ACF, especially when compared with culture. Xpert detected all the culture M. tuberculosis -positive cases and yielded three additional diagnoses in a much shorter turnaround time.…”
Section: Discussionsupporting
confidence: 92%
“…16 Similarly, a study in Nigeria reported the detection of an additional 189 M. tuberculosis- positive cases by a follow-up Xpert test among 1685 individuals with at least two smear-negative results. 17 Xpert is a diagnostic test that can be run outside centralized laboratories by individuals with minimal technical expertise. 21 In our setting, Xpert proficiency was rapidly acquired by technicians at both sites with the help of a short training course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Ethiopian study involving ACF and other interventions like ACSM, LED microscopy, contact tracing, isoniazid preventive therapy and treatment support showed better outcomes after implementation. A Nigerian study involving ACF only showed no difference in outcomes [9,10]. But for a recently published study from Myanmar that reported comparable treatment outcomes, there is limited published literature where the effect of ACF on treatment outcomes (as compared to PCF) has been assessed after adjusting for potential confounders [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recognition of these challenges, the government of Nigeria has prioritized Xpert use for people with HIV, suspected DR-TB, and children. Since introduction of Xpert in Nigeria, the few available studies have focused on its diagnostic performance in non-HIV clinical settings [12, 13]. Understanding the role of Xpert in the diagnosis of HIV-associated TB, as well as its impact on treatment outcomes, is crucial given the high mortality associated with this condition.…”
Section: Introductionmentioning
confidence: 99%